DAMPAK KESEHATAN IBU PADA KEHAMILAN REMAJA - Pintam Ayu Yastirin; Rizki Sahara; Sehmawati (Jurnal Profesi Bidan Indonesia, 2024)
Background: UNICEF noted that Indonesia is ranked 8th highest with an absolute number of child brides of 1,459,000 cases. Nationally, there are 11.2% of girls who marry under the age of 18, and 0.5% of these girls marry when they are 15 years old. Pregnant women aged 15-19 years are at greater risk of death. The risk of death during pregnancy or childbirth in women aged 10-14 years is 5 times greater and 2 times greater in women aged 15-19 years compared to women aged 20-25 years. Purpose: describe the health impacts on adolescent pregnancy in the Puskesmas Kedungjati. Method: The research method used is a descriptive survey research method, with a retrospective approach. The sample used was 43 respondents. The data was processed and analyzed using descriptive analysis to determine the frequency distribution of each variable. Results: The results of the identification of health impacts on mothers that occur due to teenage pregnancy at the Kedungjati Health Center include anemia 30.2%, bleeding 7%, preeclampsia / eclampsia 4.70%, and prolonged labor 44.2%. Results : The results of the identification of health impacts on mothers that occur due to teenage pregnancy at the Kedungjati Health Center include anemia 30.2%, bleeding 7%, preeclampsia / eclampsia 4.70%, and prolonged labor 44.2%. Conclusion : The risk of pregnancy in adolescents can increase maternal mortality, so it can be prevented by increasing the age of marriage